Exploring Stability of Ijarah Financing Market in Full Fledged Islamic Banks - Kalim, Dr Rukhsana; Arshed, Dr Noman (International Journal of Contemporary Economics and Administrative Sciences, 2023)
Ijarah contract is apparent analogues to conventional lease contract for customers, but in essence, it is different. Many empirical studies have worked on the issues and acceptability of Ijarah. However, the exploration of demand and supply based determinants of Ijarah is overlooked. This study is designed to find such determinants using the bank-based indicators from financial statements and macroeconomic data for countries with full-fledged Islamic banks. This study has used Panel FGLS model to estimate the demand for Ijarah and supply of Ijarah models using determinants via theoretical model and empirical literature. The result of the study is instrumental in determining the equilibrium Ijarah and future trends in terms of under- or over-supply of Ijarah. Further, this study has identified the price elasticity of demand and supply for the case of Ijarah financing. Islamic banks can identify their operational strategies based on the elasticity of their Ijarah product.